2007
DOI: 10.1146/annurev.cellbio.22.010605.093554
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin Regulation of Cellular Morphology

Abstract: Semaphorin proteins, although initially characterized as repulsive neuronal guidance cues, are now appreciated as major contributors to morphogenesis and homeostasis for a wide range of tissue types. Semaphorin-mediated long- and short-range repulsive, and attractive, guidance has profound influences on cellular morphology. The diversity of semaphorin receptor complexes utilized by various semaphorin ligands, the ability of semaphorins themselves to serve as receptors, and the myriad of intracellular signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
370
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(374 citation statements)
references
References 131 publications
3
370
0
1
Order By: Relevance
“…In the nervous system, neuropilin-1 acts as a receptor for Sema3A and guides the directional motility of axonal growth cones (Kolodkin et al, 1997;Turner et al, 2004;Tran et al, 2007). Sema3A signaling requires the formation of neuropilin-1 and Plexin-A receptor complexes at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nervous system, neuropilin-1 acts as a receptor for Sema3A and guides the directional motility of axonal growth cones (Kolodkin et al, 1997;Turner et al, 2004;Tran et al, 2007). Sema3A signaling requires the formation of neuropilin-1 and Plexin-A receptor complexes at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we describe the identification of neuropilin-1, a receptor for the semaphorin family of axon guidance molecules, as pro-migratory and address its role in GBM cell migration. Semaphorin3A (Sema3A) is the founding member of this family and acts as a repulsive signal for several types of developing neurons (Tran et al, 2007). On binding to neuropilin-1 and its co-receptor PlexinA1, Sema3A activates a signal transduction cascade that controls F-actin dynamics through activation of small GTPase Rac1 (Kolodkin et al, 1997;Turner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Repulsive signals from semaphorin-bound plexins are critical for proper axonal pathfinding and target innervation during neural development, and also play important roles in regulating cell migration, vascular patterning, and immune responses [reviewed in (1)(2)(3)]. Malfunction of plexin signaling has been implicated in diseases such as neurological disorders and cancer, and plexins have emerged as new drug targets for these diseases (4).…”
mentioning
confidence: 99%
“…Studies of the plexin intracellular region have led to the identification of a number of signaling pathways [reviewed in (1,2,5)]. Of particular interest is the recognition that the plexin intracellular region exhibits sequence similarity to Ras GTPase-activating proteins (Ras GAPs), representing the first example of a transmembrane receptor containing a GAP domain (6,7).…”
mentioning
confidence: 99%
“…28 Semaphorins are originally described as axonal guidance repellents that induce growth cone collapse during neuronal development and subsequently recognized as attractant and repellent cues for multiple cell types. 29,30 However, they were detected in a wide variety of tissues and shown to be implicated in diverse biological processes including organogenesis, cardiovasucular development, the immune response and tumor progression. It has been suggested that the Semaphorins are also involved in the cell -cell communication between osteoclasts and osteoblasts during bone remodeling.…”
Section: Inhibition Of Coupling In the Initiation Phasementioning
confidence: 99%